Corporate social responsibility antecedents and practices as a path to enhance organizational performance: The case of small and medium sized enterprises in an emerging economy country. (24th March 2021) - Cheffi, Walid; Malesios, Chrisovalantis; Abdel‐Maksoud, Ahmed; Abdennadher, Sonia; Dey, Prasanta
Abstract: The impact of stakeholders' pressure and business uncertainties on the correlation between corporate social responsibility (CSR) and organizational performance within small and medium sized enterprises (SMEs) is under researched. This study aims to derive the correlation of CSR antecedents, CSR practices, stakeholders' pressures, business uncertainties, and organizational performance of SMEs in the UAE. The data was collected through a survey from 117 SMEs in the UAE, and analyzed using structural equation modeling. The study reveals that the level of importance SMEs attach to CSR antecedents influences positively the extent of SMEs involvement with CSR practices; and these, in turn, translate into significant performance outcomes for SMEs. Business uncertainties are proved to moderate both relationships (CSR antecedents‐CSR practices; and CSR practices‐SMEs performance); while stakeholders' pressure is found to have no moderating effect on CSR antecedent‐CSR practices relationship. The proposed framework could be adopted in any economy for enhancing performance through CSR.